Soliton solutions of coupled inhomogeneous nonlinear Schrodinger equation in plasma - Uthayakumar, A; Han, YG; Lee, SB (PERGAMON-ELSEVIER SCIENCE LTD, 2006)
We consider the coupled system of inhomogeneous damped nonlinear Schrodinger equation which explains wave propagation in plasma. We generalise the (2 x 2) Ablowitz, Kaup, Newell and Segur(AKNS) formalism and construct the linear eigenvalue problem of coupled system. We use the Bdcklund transformation method to derive explicit form of one-soliton solution. (c) 2005 Published by Elsevier Ltd.
Keywords: BACKLUND TRANSFORMATION; INVERSE METHOD; WAVES; MEDIA